Screening of behavioral problems in children using child behavior checklist (1½–5 years) - George, Amalu; Shrivastava, Jyotsna (Indian Journal of Child Health, 2022)
Background: Tremendous rise in behavioral disorders in child population demands screening at the earliest. Screening asymptomatic preschool children using validated preschool child behavior checklist (CBCL) (1½–5 years) may help in early diagnosis and treatment. Objective: The objective of the study was to assess the behavioral problems, estimate their proportion in study population, and find its association with various sociodemographic factors. Materials and Methods: An observational cross-sectional study was undertaken in which 192 children of age group 1½–5 years were selected from the outpatient department attendees of a tertiary care hospital. Validated preschool CBCL was used which has 100 statements, each scored by parents as 0=not true, 1=somewhat true, or 2=very true and categorized to CBCL empirically based scale internal problems, external problems, total problems, and CBCL-diagnostic and statistical manual of mental disorders (CBCL-DSM) oriented scale. Based on total score, they were categorized to normal, borderline, and clinical range for CBCL both scales. Sociodemographic risk factors were recorded. Results: The overall proportion for behavioral disorder was 16% in studied population. Autism spectrum problems constitute highest (13%) of CBCL-DSM oriented scale problems. CBCL empirically based scale external problems are more in boys (16.3%) than girls (6.8%) in the clinical range (p=0.01). Conclusion: High proportion (16%) of behavioral disorders in preschool children, especially in boys, points toward need of early screening and intervention.